Isomeric Cross Section Study of Neutron Induced Reactions on Ge Isotopes - Vlastou, R.; Kalamara, A.; Gkatis, G.; Stamatopoulos, A.; Chasapoglou, S.; Kokkoris, M.; Axiotis, M.; Lagoyannis, A.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2020)
In the present work, natural Ge targets have been irradiated by neutron beams of 17.7 and 19.3 MeV, at the 5MV tandem accelerator of NCSR "Demokritos". The cross section of the 72,74Ge(n,α)69,71Zn and 76Ge(n,2n)75Ge reactions, leading to the population of isomeric states, has been deduced with respect to the 27Al(n,α)24Na and 93Nb(n,2n)92mNb reference reactions. After the neutron irradiations, the induced γ-ray activity of the Ge target and reference foils, was measured with high-resolution HPGe detectors.